MODEL PENDIDIKAN KARAKTER SISWA MELALUI PEMBELAJARAN BERBASIS SEKOLAH RAMAH ANAK DI MIN 1 JOMBANG: MODEL PENDIDIKAN KARAKTER SISWA MELALUI PEMBELAJARAN BERBASIS SEKOLAH RAMAH ANAK DI MIN 1 JOMBANG - Hidayat, Ahmad; Mahsun, Ali (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
Abstract: This article discusses student character education models through child-friendly school-based learning in MIN 1 Jombang. Using descriptive qualitative research with data collection methods using observation techniques, interviews and documentation and data analysis using data reduction, data presentation and drawing conclusions, the results of the study show that the character education model of students through child-friendly school learning in MIN 1 Jombang: by getting used to things positive in learning activities include: a) Responsible; b) Appreciate Friends; c) Dhuha Prayer in congregation; d) Kissing Master's hand; inhibiting factors and supporting models of student character education through child friendly school learning in MIN1 Jombang: inhibiting factors: a) educating factors; 2) family and community factors; and supporting factors lie in adequate human resources and are committed to shaping the character of students.